2007
DOI: 10.1108/rjta-11-02-2007-b006
|View full text |Cite
|
Sign up to set email alerts
|

Peel Test: A Tool to Assess The Stickiness of Honeydew Sugar

Abstract: People involved in the cotton industry, from growers to spinners, have been concerned about the problem of stickiness encountered during cotton processing from fibres to yarn. Many methods have been successfully developed to identify and measure stickiness and also to reduce the effect of these contaminations. Yet due to the poor fundamental scientific knowledge regarding the mechanisms of sugar adhesion on fibres, the major part of these methods is empirically based. Today, gaining knowledge about stickiness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…1). Amara et al (2007) also found that glucose produced stronger adhesion than sucrose when coated onto cotton fibers. Sucrose is composed of a glucose molecule bonded to a fructose molecule so the adhesion of glucose and sucrose would be expected to be similar.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…1). Amara et al (2007) also found that glucose produced stronger adhesion than sucrose when coated onto cotton fibers. Sucrose is composed of a glucose molecule bonded to a fructose molecule so the adhesion of glucose and sucrose would be expected to be similar.…”
Section: Resultsmentioning
confidence: 87%
“…1). Amara et al. (2007) also found that glucose produced stronger adhesion than sucrose when coated onto cotton fibers.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations